Picturing North African Cities in the Sixteenth Century - Manfrè, Valeria (Eikonocity. Storia e Iconografia delle Città e dei Siti Europei, 2018)
This article provides an approach to North African urban landscapes of the sixteenth century. To that end, it focuses primarily on the views in the Civitates orbis terrarum by Georg Braun and Franz Hogenberg, which are explored through a comparative analysis to other contemporary graphic materials. The purpose is to deepen our understanding of the image of the city by looking at the methods used to represent the city during the Renaissance, the importance and degree of verisimilitude that these views were expected to achieve through a language that relied on direct, in-situ observation.